Proposed audit procedures to re-evaluate oil and gas pipelines in accordance with international financial reporting standards(Retrieved search) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to identify what revaluation is in terms of concept, objectives, and importance, and to explain the requirements for revaluation in accordance with international financial reporting standards. Identify the theoretical framework for auditing procedures through the concept, definition, and importance. Establish procedures for auditing the revaluation of oil and gas pipelines by proposing procedures for auditing the revaluation. According to international financial reporting standards, The problem of the research was that there are special requirements for carrying out audit work for the revaluation process of oil and gas pipelines, considering the departure from the principle of historical cost to the principle of accounting measurement that allows the revaluation of assets, as there is no audit program approved by the Federal Office of Financial Supervision. To audit the re-evaluation of oil and gas pipelines in accordance with international auditing standards, which were re-evaluated in accordance with international financial reporting standards, the researchers reached a set of conclusions, the most prominent of which is the absence of an audit program approved by the Federal Office of Financial Supervision that meets the requirements for re-evaluating oil and gas pipelines in accordance with International Financial Reporting Standards. Accordingly, the researchers proposed several recommendations, the most important of which is adopting an audit program based on international auditing standards to audit the re-evaluation of oil and gas pipelines in accordance with international financial reporting standards.